Evaluation of Online Anatomy Education Given in Medicine and Dentistry Faculties of Universities During Covid-19 Pandemic with Student Feedback - ŞENOL, Deniz; TOY, Şeyma; CANBOLAT, Mustafa; PEKTAŞ, Murat (Konuralp Medical Journal, 2021)
Objective: We are experiencing the effects of the Covid-19 pandemic on the whole world. All educational facilities have been negatively affected in this process. In this study, the aim was to evaluate online anatomy education during the Covid-19 pandemic with students’ feedbacks and it was questioned whether it would be efficient to use online education more actively in the following years. Methods: A total of 1127 first and second-year students from dentistry faculty and medicine faculty of Düzce, Karabük, and İnönü universities were included in the study. The survey prepared in “Google Forms” was sent online to students via the “Whatsapp” application. Descriptive statistical analyses were used in data. Results: According to analysis results, it was found that the students agreed on the content and efficiency of online anatomy education and it was found that they thought anatomy theoretical courses should not be conducted only after the pandemic is over. It was found that medicine faculty students placed more importance on anatomy education in terms of professional aspects. Conclusions: As a result, we believe that the online anatomy education students receive is important in terms of their professional development. However, we believe that it won’t be possible for online anatomy education to replace face-to-face education. This study will be a resource for studies to be conducted in medicine and health sciences fields in terms of online education.
Keywords: Health Care Administration; [No Keywords]; Anatomi; Online Eğitim; Covid-19 Pandemisi; Sağlık Kurumları Yönetimi; Anatomy; Online Education; Covid-19 Pandemic; 4. Education; 3. Good health